1988
DOI: 10.1177/030006058801600106
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics of Loratadine in Normal Geriatric Volunteers

Abstract: The pharmacokinetics of loratadine, a non-sedating anti-histamine, were studied in 12 normal geriatric volunteers. In an open label fashion, each volunteer received one 40 mg loratadine capsule. Blood was collected prior to and at specified times (up to 120 h) after dosing. Plasma loratadine concentrations were determined by a specific radioimmunoassay and those of an active metabolite, descarboethoxyloratadine, by high performance liquid chromatography. Concentrations of loratadine in the disposition phase we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…While the reason for the inconsistent efficacy of loratadine is not clear, one possible explanation is a variability in its hepatic metabolism to desloratadine, a compound which possesses 2.5 to 10 times the antihistaminic activity of loratadine in animal models [9,10]. From the work of Hilbert and colleagues [11], peak plasma levels of loratadine occur 1 1 / 2 h after oral dosage while those of desloratadine are stated to occur in under three hours [9]. Thus, while an interval of 4 h between dosing and testing should have been sufficient for the absorption of loratadine and its metabolism to desloratadine, any delay in the hepatic metabolism of the parent drug in some individuals would result in a slower onset of action.…”
Section: Introductionmentioning
confidence: 99%
“…While the reason for the inconsistent efficacy of loratadine is not clear, one possible explanation is a variability in its hepatic metabolism to desloratadine, a compound which possesses 2.5 to 10 times the antihistaminic activity of loratadine in animal models [9,10]. From the work of Hilbert and colleagues [11], peak plasma levels of loratadine occur 1 1 / 2 h after oral dosage while those of desloratadine are stated to occur in under three hours [9]. Thus, while an interval of 4 h between dosing and testing should have been sufficient for the absorption of loratadine and its metabolism to desloratadine, any delay in the hepatic metabolism of the parent drug in some individuals would result in a slower onset of action.…”
Section: Introductionmentioning
confidence: 99%
“…62 De referir, ainda, que poderá haver uma potenciação de efeitos adversos com o uso de ciclosporina e corticoides sistémicos, particularmente em doentes geriátricos com hipertensão arterial e baixa taxa de filtração glomerular. 63 Relativamente às grávidas e lactantes, algumas doentes com UC refratária referem uma resolução espontânea quando engravidam com recorrência no pós-parto, enquanto outras têm agravamento das queixas de urticária durante a gravidez. 64 Embora seja boa prática clínica evitar tratamentos durante a gravidez, nas doentes com sintomas de maior intensidade alguns tratamentos podem ser efetuados sem risco embriogénico ou teratogénico.…”
Section: Situações Particularesunclassified
“…The carbamate moiety of loratadine was hydrolyzed to form the active metabolite, descarboethoxyloratadine (desloratadine) (Katchen et al 1985;Hilbert et al 1988). As the parent compound and metabolite are both pharmacologically active, the pharmacokinetic profiles of loratadine and desloratadine were investigated after a single oral dose of 5 mg loratadine was administered to 18 healthy children aged 3.8 + 1.1 years (Salmun et al 2000).…”
Section: Loratadinementioning
confidence: 99%
“…The same adult volunteers from the previous study also received a 40 mg dose of loratadine after a 1-week washout period of the lower dose. Comparison of pharmacokinetic data for loratadine in the young adults to data in 12 healthy elderly subjects (66 to 78 years; mean + SD not available) who also received a 40 mg dose of loratadine orally (Hilbert et al 1988) indicated that C max values were 3.8-fold higher in the elderly (Table 9). Furthermore, the AUC and t 1/2 , respectively, were 4.1-fold and 4.9-fold higher in subjects with advanced age vs. the young volunteers.…”
Section: Kinetic and Dynamic Data To Assess Risk In Sensitive Groupsmentioning
confidence: 99%